EFEK HIPOTENSIF DARI ACEi DAN ARB PADA PASIEN DIABETES MELLITUS DAN HIPERTENSI DI RSUD. ABDUL WAHAB SYAHRANIE SAMARINDA - Rusdiati Helmidanora; Triswanto Sentat (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
More than two-thirds of patients with type 2 diabetes also experience hypertension whose development coincides with hyperglycemia, where each disease has a tendency to influence the increased risk of other diseases. Sundry new guidelines, such as the National Joint Committee 8, the American Diabetes Association recommend blood pressure targets in the diabetic population of <140/90 mmHg to reduce cardiovascular risk and prevent the progression of nephropathy. This study aims to determine whether there is a difference in achieving blood pressure target < 140/90 mmHg according to Join National Committee 8 between ACEi and ARB in patients with type 2 diabetes with hypertension. This research was conducted using a retrospective at internist clinic of Abdul Wahab Syahranie hospital, by taking secondary data from the medical record from blood pressure o 49 outpatients received a single antihypertensive either drug ACEi 29 people or ARB 34 people. This study showed that the achievement of target blood pressure by <140/90 mmHg (JNC 8 guideline) between ACEi 7 (28%) and ARB 5 (20,8%) group and it can be concluded that between ACEi and ARB drugs(P=0.5) there was no differsignificantly in achievement blood pressure target on type 2 diabetes with hypertension.